(untitled) (Al-Qamar, 2023)
Akhtar Raza Salimi’s novels "Jage Hain Khwab Mein" and "Jander" are mirror of the cultural phenomena born from the establishment of the Islamic Empire of Syed Ahmad Shaheed in the mountain ranges of Punjab and Khyber Pakhtunkhwa and the Hazara Valley and the Mujahideen’s resistance to the British and the Sikhs. These novels describe the existential crisis and the importance of the characters and events in terms of symbolism. By showing the components of the decaying civilization and struggling with the oppression of the industrial era, Akhtar Raza Salimi has highlighted the freedom of human temperament and the freedom of personal choice. He presents in an allegorical way that the industrial era prevented man from living as a free creature.